TERAPI MUSIK DAN RELAKSI NAFAS DALAM TERHADAP PENURUNAN NYERI POST OP FRAKTUR - Andi Nuraina Sudirman; Inne Ariane Gobel (-, 2021)
Music therapy can reduce pain by distrcting a person’sconcern on the pain itself. Deep breathing relaxation technique is believed to be able to stimulate body to release apoiod endogen which is endorphin and encphalin that are useful for decreasing the pain. Music therapy and deep breathing relaxation techinique can affect the decrease of the postoperative wound pain fracture. The objective of this researchin general is to determine the in fluence of music therapy  and deep breathing relaxation to decreasepost operative pain fracture in surgery room. The sample of this research consists of16 respondents. Ststistically, paired t test value is significant that is sig (2 tailed) is 0,000.since the value of sig is (2 tailed)<α (0,05) then it can be concluded that H0 is rejected and Ha is accepted. Therefore in another words there is in the influence of music therapy and deep breathing relaxation to decrease the pain.